Supporting vulnerable babies and young children interventions for working with trauma, mental health, illness and other complex challenges - Bunston, Wendy; Jones, Sarah J. (Social worker) (Jessica Kingsley Publishers, 2020)
The diverse challenges that clinicians and children's workers tasked with safeguarding babies and young children face are complex, and this unique book looks at effective, evidence-informed approaches to working across a wide range of issues. It outlines relevant theory and good practice, gathering case examples from around the world to illustrate what interventions look like in direct practice. Leading contributors address a wide range of challenges, including babies and very young children who have a serious illness, have complex diagnoses, or have been exposed to violence or adversity in early childhood. This is an essential guide for those who work to support and safeguard the welfare of babies and very young children, including professionals in health care, social work, mental health and child protection settings"--